2016
DOI: 10.5830/cvja-2015-059
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic abnormalities and dyslipidaemic syndrome in children with sickle cell anaemia

Abstract: SummaryBackgroundLipid and electrocardiographic (ECG) abnormalities have been reported in adults with sickle cell anaemia (SCA) and may reflect underlying structural and/ or functional damage. However, the relationship between ECG and lipid abnormalities among children with sickle cell disease is not fully understood.ObjectivesTo compare the steady-state lipid and ECG abnormalities in children with SCA to the controls and examine the hypothesis that lipid abnormalities are closely related to electrocardiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 20 publications
4
23
1
Order By: Relevance
“…In men, TG was related to ECG parameters except for QTc interval and S amplitude but in women, it had significant associations with heart rate, R amplitudes, Sokolow-Lyon index, QT interval, P and QRS axis. Although we did not find any correlation between TG and PR interval in women and a slight significant relationship in men but Adegoke et al, 39 reported that triglyceride had a positive correlation with the PR interval (r = 0.3). This difference may be due to their different population and age because they have studied children with sickle cell anemia.…”
Section: Each Metabolic Syndrome Component and Ecg Parameterscontrasting
confidence: 89%
“…In men, TG was related to ECG parameters except for QTc interval and S amplitude but in women, it had significant associations with heart rate, R amplitudes, Sokolow-Lyon index, QT interval, P and QRS axis. Although we did not find any correlation between TG and PR interval in women and a slight significant relationship in men but Adegoke et al, 39 reported that triglyceride had a positive correlation with the PR interval (r = 0.3). This difference may be due to their different population and age because they have studied children with sickle cell anemia.…”
Section: Each Metabolic Syndrome Component and Ecg Parameterscontrasting
confidence: 89%
“…The PCV, haemogblogin concentration and red cell counts were significantly lower among sickle cell disease subjects, similar to findings by Adegoke, this could be due to the ongoing haemolysis, nutritional deficiencies, frequent crises and repeated infections they are exposed to [7]. This study also showed higher values of white blood cell and platelet in the cases compared with control.…”
Section: Pattern Of Laboratory Parameters In the Study Participantssupporting
confidence: 88%
“…Eleven of these articles had two or more conditions. Comorbidities such as diabetes (37,76,77), hyperlipidemia (95,96), and thyroid dysfunction (97) may affect ECGs and obscure the true effect of hypertension on ECGs. Future studies comparing normotensive individuals to individuals with hypertension need comprehensive exclusion criteria to remove participants with comorbidities from the study population.…”
Section: Discussionmentioning
confidence: 99%